Coordination Optimization of the First and Last Trains' Departure Time on Urban Rail Transit Network. (26th December 2013) - Zhou, Wenliang; Deng, Lianbo; Xie, Meiquan; Yang, Xia
Abstract : Coordinating the departure times of different line directions' of first and the last trains contributes to passengers' transferring. In this paper, a coordination optimization model (i.e., M1) referring to the first train's departure time is constructed firstly to minimize passengers' total originating waiting time and transfer waiting time for the first trains. Meanwhile, the other coordination optimization model (i.e., M2) of the last trains' departure time is built to reduce passengers' transfer waiting time for the last trains and inaccessible passenger volume of all origin-destination (OD) and improve passengers' accessible reliability for the last trains. Secondly, two genetic algorithms, in which a fixed-length binary-encoding string is designed according to the time interval between the first train departure time and the earliest service time of each line direction or between the last train departure time and the latest service time of each line direction, are designed to solve M1 and M2, respectively. Finally, the validity and rationality of M1, M2, and their solving genetic algorithms are verified with numerical analysis, in which the effects of the parameters in M1 and M2 on coordination optimization result are analyzed.